Description of the last instar larva of Acanthallagma caeruleum Williamson & Williamson, 1924 (Odonata: Coenagrionidae) - Alvarez-Alvarez, Karen Lineke; Bota-Sierra, Cornelio A.; Molineri, Carlos (Zootaxa, 2025)
The last larval instar of Acanthallagma caeruleum Williamson & Williamson, 1924 is described and illustrated for the first time based on a reared female collected in the Colombian Amazon region (Caquetá department). This is the first larva known for this genus. The general aspect of the larva resembles that of some Oxyagrion Selys, 1876 and Acanthagrion Selys, 1876 species and presents the following unique combination of features: 1 pair of premental setae, stout spines mounted on elevated sockets in body and legs, caudal lamellae lanceolate and 0.86–0.90 the length of abdomen, with marked nodus and sulcus.